ANALISIS KOMPARATIF TANAMAN PERKEBUNAN DI PROPINSI RIAU - Octavianus Agustus; Masyhuri Masyhuri; Mas Soedjono (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 1999)
Plantation crop particularly rubber, cconut and oil palm are important export commodities because they are reliable to increase the foreign exchange and plantation farmers income.